Coronary artery disease risk reduction in HIV-infected persons: a comparative analysis. Issue 4 (2nd April 2016) - Okeke, Nwora Lance; Chin, Tammy; Clement, Meredith; Chow, Shein-Chung; Hicks, Charles B.
ABSTRACT: Despite an increased risk of coronary artery disease (CAD) in persons infected with human immunodeficiency virus (HIV), few data are available on primary prevention of CAD in this population. In this retrospective cohort study, HIV-infected patients treated in an academic medical center HIV Specialty Clinic between 1996 and 2010 were matched by age, gender, and ethnicity to a cohort of presumed uninfected persons followed in an academic medical center Internal Medicine primary care clinic. We compared CAD primary prevention care practices between the two clinics, including use of aspirin, HMG-CoA reductase inhibitors ("statins"), and anti-hypertensive drugs. CAD risk between the two groups was assessed with 10-year Framingham CAD risk scores. In the comparative analysis, 890 HIV-infected persons were compared to 807 controls. Ten-year Framingham CAD Risk Scores were similar in the two groups (median, 3; interquartile range [IQR], 0–5). After adjusting for relevant risk factors, HIV-infected persons were less likely to be prescribed aspirin (odds ratio [OR] 0.53; 95% confidence interval [CI], 0.40–0.71), statins (OR, 0.70; 95% CI, 0.53–0.92), and anti-hypertensive drugs (OR, 0.63; 95% CI, 0.50–0.79) than persons in the control group. In summary, when compared to demographically similar uninfected persons, HIV-infected persons treated in an HIV specialty clinic were less likely to be prescribed medications appropriate for CAD risk reduction. Improving primary preventative CAD care in HIV specialty clinic populations is an important step toward diminishing risk of heart disease in HIV-infected persons.